2021
DOI: 10.1093/ageing/afab154
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour change interventions to increase physical activity in hospitalised patients: a systematic review, meta-analysis and meta-regression

Abstract: Background Low physical activity levels are a major problem for people in hospital and are associated with adverse outcomes. Objective This systematic review, meta-analysis and meta-regression aimed to determine the effect of behaviour change interventions on physical activity levels in hospitalised patients. Methods Randomised controlled trials of behaviour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 62 publications
1
16
0
1
Order By: Relevance
“…Pain intensity, PCS magnification, and physical activity levels improved significantly in the intervention group compared to those in the control group. A systematic review revealed the effect of behavioural change interventions on physical activity levels in hospitalised patients, and the most common equipment used was accelerometers for feedback [ 39 ]. In addition, pedometers have been suggested as a successful motivational tool for increasing ambulatory activity in older adults [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pain intensity, PCS magnification, and physical activity levels improved significantly in the intervention group compared to those in the control group. A systematic review revealed the effect of behavioural change interventions on physical activity levels in hospitalised patients, and the most common equipment used was accelerometers for feedback [ 39 ]. In addition, pedometers have been suggested as a successful motivational tool for increasing ambulatory activity in older adults [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the study by Pupier and colleagues, the patients were only included if they did not have peripheral neuropathy, arterial diseases or articular pathology, and the sample may represent more healthy patients than those who were included in the present study. Patients' goal setting and feedback methods have also been suggested to support behavioral changes and improve outcomes [22]. As exercise training may reduce the blood glucose in patients with T2DM, there is a risk of hypoglycemia, especially if the patients are treated with insulin.…”
Section: Discussionmentioning
confidence: 99%
“…As education, goal-setting, feedback and telephone interventions have been reported to be effective in behaviour change in previous studies, [15][16][17] these techniques were used in this study.…”
Section: Behaviour Change Techniquesmentioning
confidence: 99%